Strategic management of the portfolio of urban real estate: research of the current scientific knowledge - Lucia Dobrucká; Martin Maštálka; Vladimíra Šilhánková (Acta Polytechnica CTU Proceedings)
Municipalities possess a wide range of real estate. However, land, buildings, and premises must not only be managed individually, but also optimized and strategically developed as a comprehensive portfolio linked to the objectives of public administration activities and, of course, to the development plans of a particular municipality. Nevertheless, a comprehensive view of the issue of managing and building a real estate portfolio in public administration is missing. This is evidenced by the lack of a methodology that would help local authorities with the task. Thus, a quantitative analysis of scientific publications was conducted, dealing with the issue of strategic management of real estate portfolios at the city level, both within the Czech Republic and throughout the world. This article aims to present a qualitative search of the content of scientific publications, thereby contributing to the creation of a foundation for further systematic research into this issue.